EVALUATION OF ORGANIC MATTER REMOVAL EFFICIENCY FROM PIGGERY WASTEWATER TREATMENT BY THE UPFLOW SLUDGE BLANKET FILTRATION (USBF) SYSTEM - Văn Thoại Mỹ; Nguyễn Minh Kỳ; Bùi Trâm Anh (Tạp chí Khoa học Đại học Đà Lạt)
The microbial bed fixed upflow sludge blanket filtration (USBF) system was operated for about 100 days and steady state data were collected. The results showed that the USBF system had a better ability in term of organic matter removal. In this study, the removal of pollutants from piggery wastewater was evaluated in the USBF reactor at hydraulic retention time (HRT) of 6-15 hours and solid retention time (SRT) of 20 days. The experimental study indicates the average removal efficiency of organic matter with HRT of 12 hours. The results showed that the average removal efficiency for Biological Oxygen Demand (BOD5), Chemical Oxygen Demand (COD) were over 94.2% and 93.3% respectively. USBF as an advanced biological process had a pollutants removal efficiency from piggery wastewater.